The Existence of Financial Management Patterns in The Public Service Agencies - Imron Rizki A.; Ma'adul Yaqien Makkarateng; Mustakim La Dee (Al-Bayyinah, 2022)
This study discusses the financial management of the Public Service Agency (Badan Layanan Umum/BLU) in providing flexibility in the form of the flexibility to implement healthy business practices, improve services to the community and promote general welfare and educate the nation's life. By using descriptive analysis method and normative juridical approach, this research intends to describe something that is the object of critical research through qualitative analysis. Financial Management in BLU is widely applied in several government agencies that provide public services such as hospitals and government-owned higher education providers. Although the management of BLU is carried out separately from the parent agency, it must still be subject to and comply with the applicable laws and regulations regarding state finances.